A comparative analysis of energy performance for external wall types in practice - Limoncu, Sevgul; Serbest Yenidunya, Seda (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2022)
Urban regeneration has accelerated after the establishment of the Law on Transformation of Areas Under Disaster Risk and has been carried out intensively. Building renewal, especially at a parcel scale, cannot deal with environmental problems on an urban scale and accordingly, the sustainability principles cannot be addressed holistically. Since building renewal at a parcel scale affects a large area throughout the city, it is required to include design criteria for environmental impacts. In this context, it is important to reduce heating and cooling energy consumption, which constitutes a large part of the total energy consumed in the use of buildings, and to take environmental measures. This study aims to analyse the energy performance of external walls in new buildings constructed after 2012 in the Suadiye Neighbourhood and to determine the most appropriate wall section. For this purpose, external walls were determined with a field study, and scenarios related to building orientation, the distance between buildings and external wall sections were created on a sample building. The scenarios were analysed with DesignBuilder simulation and TS825 calculation. The results for the scenarios were evaluated comparatively. The study differs from existing studies with its scope by dealing with both building renewal and energy efficiency and analysing the external wall types in different scenarios with Design Builder and TS825 for the temperate humid climate zone. As a result of the study, the most suitable wall sections for the scenarios were determined and suggestions were developed. The results of the study contribute to the country's economy by ensuring the efficient use of resources.
Keywords: Building renewal; DesignBuilder; energy consumption; TS825; urban regeneration; THERMAL PERFORMANCE; BUILDINGS; COST; Architecture